2022
DOI: 10.1177/10760296211070580
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pre-delivery Coagulation Indicators and Invasive Placenta Accreta Spectrum

Abstract: Objectives To analyze the association between pre-operational coagulation indicators and the severity of placenta accreta spectrum (PAS), as well as blood loss volume during operation. Methods Hospitalized patients of the obstetric department in a major hospital from 2018 to 2020 who were clinically and/or pathologically diagnosed with invasive PAS were included. Univariate and multivariate logistic regression and Poisson regression models were used to quantify the association between each of the 6 coagulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…4 Continuous outcomes (hospital LOS and adjusted cost) were dichotomized by setting the cutoff value as a rounded number near the 75th percentile. 44 For each outcome measure, we first applied a predefined adjustment model [45][46][47] to assess the adjusted association of placenta previa with the risk of PAS outcomes. The following factors were included along with placenta previa in the predefined model: age, year, race and ethnicity, obesity status, Charlson Comorbidity Index score, PAS severity, previous cesarean delivery, multiparity, gestational weeks, the use of assisted reproductive technology, multiple gestation, hospital bed size, and hospital teaching status.…”
Section: Discussionmentioning
confidence: 99%
“…4 Continuous outcomes (hospital LOS and adjusted cost) were dichotomized by setting the cutoff value as a rounded number near the 75th percentile. 44 For each outcome measure, we first applied a predefined adjustment model [45][46][47] to assess the adjusted association of placenta previa with the risk of PAS outcomes. The following factors were included along with placenta previa in the predefined model: age, year, race and ethnicity, obesity status, Charlson Comorbidity Index score, PAS severity, previous cesarean delivery, multiparity, gestational weeks, the use of assisted reproductive technology, multiple gestation, hospital bed size, and hospital teaching status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that smoking causes hypercoagulability and increased risk of thrombosis, and during pregnancy, due to physiological adaptation, the hemostatic system presents as a relatively hypercoagulable state with decreased anticoagulation function; however, studies in women with PAS have shown that they have hypocoagulability and hyperfibrinolysis [ 36 ]; therefore, the mechanism of the association between smoking and the PAS is unknown. However, the systemic inflammation induced by air pollution affects female genital tract damage, including damage to the endometrial and myometrium epithelium, and leads to poor decidualization [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al investigated the feasibility of routine coagulation testing prior to delivery and verified the association between prothrombin time, D-dimer, and fibrin degradation product with blood loss volume in severe PAS cases, which is the most common form of severe maternal morbidity. 22 The IS-PAS referred to these findings in their review of hemostatic considerations in PAS 23 and recommended the provision of prepartum and intrapartum coagulation testing, including complete blood count, fibrinogen levels, standard coagulation parameters, and D-dimers. In contrast, conservative management strategies may leave the placenta untouched; however, the coagulation activity induced by local trophoblasts may increase the consumption of fibrinogen and increase the levels of D-dimer, thus increasing the risk of secondary hemorrhage.…”
Section: Etiological Investigations Have Shed New Light On the Predic...mentioning
confidence: 99%
“…Guo et al . investigated the feasibility of routine coagulation testing prior to delivery and verified the association between prothrombin time, d -dimer, and fibrin degradation product with blood loss volume in severe PAS cases, which is the most common form of severe maternal morbidity 22 . The IS-PAS referred to these findings in their review of hemostatic considerations in PAS 23 and recommended the provision of prepartum and intrapartum coagulation testing, including complete blood count, fibrinogen levels, standard coagulation parameters, and d -dimers.…”
Section: Etiological Investigations Have Shed New Light On the Predic...mentioning
confidence: 99%